Effect of biocompatible nucleants in rapid crystallization of natural amino acids using a CW Nd:YAG laser. Issue 1 (December 2018) - Thippeshappa, Shilpa; George, Sajan; Bankapur, Aseefhali; Chidangil, Santhosh; Mathur, Deepak; Abdul Salam, Abdul Ajees
Abstract Laser-induced crystallization is emerging as an alternative technique to crystallize biomolecules. However, its applications are limited to specific small molecules and some simple proteins, possibly because of the need to use high-intensity, pulsed lasers and relatively long laser irradiation time. Both these factors tend to denature biological molecules. If the laser-intensity and time required to crystallize biomolecules were to be reduced, laser-induced crystallization may well become of widespread utility. We report here the crystallization of nineteen natural amino acids by a laser-induced method in combination with one of three nucleants: aluminum, coconut coir, and peacock feather barbule. We have utilized a low-power, continuous wave (CW) Nd:YAG laser (λ = 1064 nm). The advantages of our method are (i) the use of very small laser powers (60 mW), and (ii) the ability to obtain diffraction quality crystals within a mere few seconds. For most amino acids our method yields several orders of magnitude reduction in crystallization time. The use of biocompatible nucleants like coir fibres and peacock feather barbules are novel; their non-toxic nature may find broad applicability in rapid crystallization of diverse biological molecules.